HEAVY MINERAL DISTRIBUTION PATTERNS AND CHARACTERISTICS OF SEA FLOOR SURFICIAL SEDIMENT AT EAST BALI WATERS, BALI PROVINCE - I Wayan Lugra (BULLETIN OF THE MARINE GEOLOGY, 2011)
Analyses result of the heavy minerals that was took from beach sediments and sea floor surficial sediments was founded ten heavy minerals namely hematite, magnetite, limonite and rutile from oxide and hydroxide group, pyroxene, amphibol and zircon from silicate group, biotit from mica group, barite from sulfide group and dolomite from carbonate group. From 10 minerals identified, only magnetit distributes in the whole area, with the highest percentage of 34,15% in the sea and 35,14 % on beaches. Other heavy minerals distribute locally with the percentage of less than 0,01 %. Grain size analyses result of sea floor surficial sediment had identified six units sediment such as sand, sand with few gravel, sandy gravel, gravely sand, gravel and reef. Distribution area of the six units sediment as follows sand and sandy gravel are occupied 25 % respectively of the study area, reef 20%, sand 15 %, gravel 10 % and gravely sand occupied 5%. The best sediment for making art goods is sand sizes which is rich of heavy minerals such as magnetite, hematitre, limonite, zircon, pyroxene and amphibol. If will be exploited of the sand sediment on beach or sea floor surficial sediment, should be considering of the environment sustainable. Keyword: grain size analyses, heavy mineral, seafloor surficial sediment, besach sediment, Karang Asem Hasil analisis mineral berat dari sedimen pantai dan permukaan dasar laut dijumpai sepuluh jenis mineral berat yaitu magnetit, hematit, limonit, rutil dari kelompok oksida & hidroksida, piroksen, ampibol, sirkon dari kelompok silikat, biotit dari kelompok mika, barit dari kelompok sulfida dan dolomit dari kelompok karbonat. Dari sepuluh jenis mineral berat yang teridentifikasi hanya magnetit yang sebarannya merata di seluruh daerah penyelidikan baik di laut maupun di pantai dengan persentase tertinggi 34,15 % di laut dan 35,14% di pantai, sedangkan sembilan mineral lainnya sebarannya tidak merata atau setempat-setempat dengan persentase umumnya di bawah 0,01 %. Hasil analisis besar butir sedimen permukaan dasar laut dapat di bedakan menjadi 6 satuan yaitu pasir, pasir sedikit krikilan, pasir krikilan, krikil pasiran, krikil dan terumbu karang. Luas sebaran ke enam jenis sedimen tersebut terhadap luas daerah penelitian adalah pasir sedikit krikilan menempati 25%, pasir krikilan 25%, terumbu karang 20%, pasir 15%, krikil 10% dan menempati pasir krikilan 5%. Jenis sedimen yang baik untuk pembuatan benda seni adalah sedimen berukuran pasir dengan kandungan mineral berat yang tinggi seperti magnetit, hematit, limonit, sirkon, piroksen, dan ampibol. Bila akan dilakukan eksploitasi terhadap sedimen jenis pasir baik di laut maupun di pantai, harus memperhatikan kelestarian lingkungan. Kata kunci: analisis besar butir, mineral berat, sedimen permukaan dasar laut, sedimen pantai, Karang Asem